Impeachment Mechanism for The President and/or Vice President of Indonesia and United States - Firza Setiawan Putra; Bachtiar Arya Habibillah; Muhammad Fatur Khadafi; Ach. Zahid (Journal of Indonesian Constitutional Law, 2024)
In Indonesia, the impeachment process is regulated in the 1945 Constitution and Law no.  24 of 2003 concerning the Constitutional Court.  The process is initiated by the House of Representatives (DPR) which proposes impeachment if the President or Vice President is suspected of committing a violation of law, treason against the state, corruption, or disgraceful acts.  After the proposal is approved by the DPR, the Constitutional Court examines and decides whether any violations have been committed.  If the Constitutional Court declares it proven, this decision is sent back to the DPR for final approval.  After that, the People's Consultative Assembly (MPR) can dismiss the President or Vice President.  Although both countries have similar mechanisms involving parliament and the judiciary, the differences lie in the institutions involved and the stages of the process.  Impeachment reflects the principle of checks and balances in the government system to maintain the accountability of high-ranking officials.